Hearing Assessment of Medical Equipment for Health Facilities in Cameroon - Fokouo, Jean Valentin F.; Ngounou , Guy Merlin; Nyeki, Adele-Rose Ngo; Choffor-Nchinda, Emmanuel; Dalil, Asmaou Bouba; Ngom, Esthelle Geneviève Stephanie Minka; Vokwely, Jean Espoir Evehe; Nti, Albert Bernard Atsa; Kom, Martin; Njock, Louis Richard (New Horizons in Medicine and Medical Research Vol. 9, 2022)
The COVID-19 epidemic provides an opportunity for Sub-Saharan African countries to rethink their international alliances and national objectives. Having raw materials will not, in fact, contribute to progress. It can only be done by local industry. They must provide favourable conditions for the rise of local businesses in all disciplines, particularly in the food and health industries, which will support the development of other sectors. Cameroon now has all of the tools it needs to reverse hearing loss. Every year, additional otorhinolaryngologists, speech therapists, hearing aid fitters, cochlear implant surgeons, and other professionals are added to the field. The SON'OR gadget allows the country to lead the way in hearing screening. Our objective is to see the implementation of a National Universal Newborn Hearing Screening Program to aid in early detection and rehabilitation. BENDO will continue to improve and innovate in the domains of otorhinolaryngology, as well as other medical and non-medical fields. It will soon deliver, among other things, an electronic computer-based pure tone audiometer and a digital hearing aid.